Increased systemic HSP70B levels in spinal muscular atrophy infants. Issue 7 (15th May 2021) - Eichelberger, Eric J.; Alves, Christiano R. R.; Zhang, Ren; Petrillo, Marco; Cullen, Patrick; Farwell, Wildon; Hurt, Jessica A.; Staropoli, John F.; Swoboda, Kathryn J.
Abstract: Despite newly available treatments for spinal muscular atrophy (SMA), novel circulating biomarkers are still critically necessary to track SMA progression and therapeutic response. To identify potential biomarkers, we performed whole‐blood RNA sequencing analysis in SMA type 1 subjects under 1 year old and age‐matched healthy controls. Our analysis revealed the Heat Shock Protein Family A Member 7 (HSPA7) /heat shock 70kDa protein 7 (HSP70B) as a novel candidate biomarker to track SMA progression early in life. Changes in circulating HSP70B protein levels were associated with changes in circulating neurofilament levels in SMA newborns and infants. Future studies will determine whether HSP70B levels respond to molecular therapies.